Effect of Collagen-Reactive Functional Monomer on Etch-and-Rinse Adhesives. (March 2023) - Yu, S.Y.; He, X.; Tian, Z.L.; Li, K.X.; Chen, H.; Wang, H.M.; Shi, Z.S.; Zhu, S.; Cui, Z.C.
In this study, we evaluated a novel functional monomer (4-formylphenyl acrylate [FA]) that can specifically and covalently bind to the dentin collagen matrix as a potential alternative hydrophobic diluent-like monomer for improving the durability of dentin bonding. Experimental adhesives with different FA contents (0%, 10%, 20%, and 30%) were evaluated as partial substituents for the hydrophilic monomer 2-hydroxyethyl methacrylate, with the commercial adhesive One-Step (Bisco, Inc.) employed as the positive control. Their degree of conversion, viscosity, hydrophobicity, mechanical properties, and water absorption/solubility were measured as the comprehensive characterization. In situ zymographic assays were performed to determine the extent to which FA inhibits the endogenous hydrolytic activity of dentin. Finally, the bonding performances of the novel adhesives were evaluated with microtensile strength tests and scanning electron microscopy. The results showed that the incorporation of FA significantly improved the mobility of experimental adhesives attributable to the dilution property of FA. In contrast to the possible compromised rate of polymerization by hydroxyethyl methacrylate, FA exhibited typical characteristics of favorable copolymerization with polymerizable monomers in adhesives and improved the degree of conversion of experimental adhesives. The rigidity and hydrophobic properties of the phenyl framework of the FA molecule conferred superior mechanical properties and hydrolysis resistance to the novel experimental adhesives. An inhibitory effect on gelatinolytic activities within the hybrid layer was also observed in the in situ zymographic assays, even at a low FA concentration (10%). In conjunction with the significantly improved infiltration found via scanning electron microscopy, the experimental adhesives containing FA possessed significantly better-maintained microtensile strength, even after aging. Thus, the incorporation of this novel monomer endowed the experimental adhesives with multiple enhanced functionalities. These remarkable advantages highlight the suitability of the monomer for further applications in clinical practice.